EFL university students' self-directed language learning with ICT: a structural equation modelling approach* - Tubagus Zam Zam Al Arif; Urip Sulistiyo; Sri Wachyunni (Universidad de Cádiz, 2024)
The growth of information and communication technology (ICT) can enhance students' self-directed language learning (SDLL). Language learning in online settings have determined positive correlations between self-directed learning behaviour and academic achievement. This study was conducted to examine factors influencing self-directed language learning with ICT. A quantitative design was applied, which involved 1,022 pre-service teachers of English department from nine universities in Indonesia. A questionnaire was employed to collect the data, and the proposed hypotheses were examined using PLS-SEM. The PLS-SEM analysis demonstrated that the attitude towards the use of ICT mediates the influence of ICTSE, OCSE, FC, and SN on SDLLICT. The results indicated that students' attitude is the most significant variable in enhancing self-directed language learning through ICT. The study's findings are useful for both learners and educators in leveraging ICT for self-directed language learning. Students must be equipped with ICT literacy and positive attitudes towards using ICT in English language learning activities. Teachers should also be equipped with ICT skills in order to provide learning experiences that are customized to students' needs and preferences in today's digital world. Furthermore, this study provides significant implications for educators and policy makers in providing ICT infrastructure that meets the students' needs.